Comparison of clinico-radiological profile of pulmonary tuberculosis in diabetic and non-diabetic patients in a tertiary care hospital – An observational analytical study - Asif Iqbal Biswas; Arindam Ray; Amitava Pal; Saikat Banerjee; Amiya Kumar Dwari (Asian Journal of Medical Sciences, 2025)
Background: Diabetes mellitus (DM) is becoming more widely acknowledged as a significant comorbidity that negatively affects outcomes of pulmonary tuberculosis (PTB), which remains a significant worldwide health burden. The interplay between TB and DM modifies clinical, microbiological, and radiological characteristics, necessitating detailed evaluation. Aims and Objectives: The study aims to evaluate the impact of glycemic management on disease presentation and compare the clinico-radiological and microbiological profiles of PTB patients with and without DM. Materials and Methods: This observational, hospital-based study included adult patients newly diagnosed with PTB. Patients were stratified into diabetics and non-diabetics based on history and glycosylated hemoglobin levels. Data on clinical symptoms, sputum smear positivity, and chest radiographic findings were recorded. Diabetics were further categorized based on glycemic control. Statistical analyses were performed to identify differences between groups. Results: Diabetic patients had a higher prevalence of cough (98.1%), fever (87.0%), hemoptysis (35.2%), and weight loss (90.7%) compared to non-diabetics (P<0.05). Sputum positivity was significantly higher in diabetics (90%) than in non-diabetics (75%) (P<0.001). A higher bacillary load (3+smear grade) was observed in 50% of poorly controlled diabetics, compared to 30% of well-controlled diabetics and 20% of non-diabetics (P<0.001). Radiologically, diabetics showed more lower lung field involvement (31.5% vs. 10.2%) and multilobar disease (68.5% vs. 45.3%) compared to non-diabetics (P<0.05). Conclusion: More severe symptoms, larger bacillary loads, and extensive, unusual radiological presentations are linked to DM, especially when it is poorly controlled, in PTB. Hence, for the best care, early identification and stringent glycemic control are essential.